Globalisasi dan Perubahan Pengelolaan Bisnis - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2008)
Globalization become rapid because of rapidity in hussines invorem en!. Globalization improve amount and variation conipeition in the market and appearance continously change, radical, fast, and comprehensive1 New management patern is required to able stave of and progress in turbulen environment. One approach is used to bussines management in globalization era is total quality mancijemen (TQM,). TQM is management approach is used to improve long term corporate competitiveness Key words: globalization, change, business environment